The Double Burdens of Mental Health Among AIDS Patients With Fully Successful Immune Restoration: A Cross-Sectional Study of Anxiety and Depression in China - Huang, Xiaojie; Meyers, Kathrine; Liu, Xinchao; Li, Xia; Zhang, Tong; Xia, Wei; Hou, Jiahua; Song, Aixin; He, Haolan; Li, Chongxi; He, Shenghua; Cai, Weiping; et al. (Frontiers in Psychiatry, 2018)
Background Anxiety and depression continue to be significant comorbidities for people with HIV infection. We investigated the prevalence and factors associated with anxiety and depression among adult HIV-infected patients across China. Methods In this cross-sectional study, we describe clinical and psychosocial variables related to depression and anxiety in 4103 HIV-infected persons. Doctors assessed anxiety and depression by asking patients whether they had experienced anxiety or depression in prior month. Patients also completed the Hospital Anxiety and Depression (HAD) scale with score ≧ 8 on HAD-A/D consistent with anxiety or depression. Results Associations between socio-demographic, psychosocial, and ART-related clinical factors and risk of depression or anxiety were investigated using multivariable logistic regression. Among these patients (assessed 9/2014 -11/2015), 27.4% had anxiety, 32.9% had depression, and 19.0% had both. Recentness of HIV diagnoses (P=0.046) was associated with elevated odds of anxiety. Older age(P=0.004), higher educational attainment (P<0.001)，employment (P=0.001), support from family / friends (P<0.001), and sleep disturbance (P<0.001), and number of ART regimen switches(P=0.046) were associated with risk of depression, while neither sex nor transmission route showed any associations. There were no significant associations with HIV-specific clinical factors including current CD4+ T cell count and current viral load. Conclusions Prevalence of anxiety and depression is high in this cohort of treated HIV patients. Psychological and social-demographic factors, rather than HIV disease status, were associated with risk of depression and anxiety. This finding highlights the need to consider the mental health issues of HIV-infected persons even with fully successful immune restoration across China.